Performance Model: Organizational Culture, Work Environment and Creativity (Empirical Study at Sekolah Tinggi Ilmu Ekonomi Tuah Negeri) - Khotimah, Khusnul; Aima, M. Hafidz (International Journal of Advanced Multidisciplinary, 2023)
The purpose of this research is to determine and analyze the influence of organizational culture, work environment and creativity, both partially and simultaneously, on employee performance at the Sekolah Tinggi Ilmu Ekonomi Tuah Negeri. The population in this study were all employees (lecturers and employees) with the total number of sample respondents. The research method used multiple linear regression analysis and descriptive analysis. Regression analysis was carried out to determine whether the independent variables (Creativity, organizational culture and work environment) either partially or simultaneously had an effect on the dependent variable (Performance), and descriptive analysis was carried out by collecting data through the use of respondent questionnaires. The research results show that the organizational culture and work environment variables partially have no effect on performance, while the creativity variable partially has a positive and significant effect on performance. Simultaneously, the three independent variables of organizational culture, work environment and creativity have a positive and significant effect on performance at Sekolah Tinggi Ilmu Ekonomi Tuah Negeri